Proceedings of the 16th International Conference on Soil Mechanics and Geotechnical Engineering[ electronic resources geotechnology in harmony with the global environment - International Conference on Soil Mechanics and Geotechnical Engineering (16th : 2005 : Osaka) (Berlin, GW : Millpress, 2005)
PSZJBL